Analysis of face milling technology with a thermal camera by the changing of the number of revolution - Prezenszki, Dorottya; Wesser, Csaba; Bodzás, Sándor (International Journal of Engineering and Management Sciences, 2019)
The aim of the publication is the analysis of the temperature zone of cutting operation in case of face milling technology. The analyses are done considering of the changing of discreet number of revolution beside the constancy of the more technological parameters. The measuring concept will be determined. After the experiments the received thermal images will be analysed.